Japan rising : the resurgence of Japanese power and purpose - Pyle, Kenneth B. (PublicAffairs, 2007)
An analysis of Japan's political, economic, and security resurgence in the post-Cold War era, exploring how historical experiences and evolving national purposes have reshaped Japan's role in the world.